Pendampingan dan Penguatan Literasi Budaya untuk Menumbuhkan Rasa Nasionalisme Siswa di Sanggar Bimbingan Rawang Selangor Malaysia - Kiptiyah, Mariyatul; Liesdiani, Mety (Journal of Smart Community Service, 2024)
The program is a strategic investment designed to build the future of future generations by making culture an important element in their lives. Culture is seen as a legacy of the past and a source of inspiration that can drive positive change in society. Through various activities at the Rawang Guidance Studio, this program aims to cultivate a sense of love and pride for the country in students, so that they grow up with strong nationalism values. The various activities, such as folklore storytelling, playing traditional games, and Indonesian language learning, are designed to introduce and strengthen students' understanding of the nation's rich culture. Folktales, for example, are entertaining and convey moral values and local wisdom. Traditional games teach the importance of cooperation, sportsmanship, and local wisdom. At the same time, Indonesian language learning helps students better understand their mother tongue, which is an important bridge to maintaining cultural identity. The program not only aims to preserve culture but also fosters awareness of the importance of maintaining culture as a national identity. That way, culture will remain relevant and able to become a strong foothold for the students at the Rawang Guidance Center.